Growth history and facies evolution of the subis limestone - A carbonate platform exposed onshore Borneo Island, Malaysia - Dedeche, A.S. (European Association of Geoscientists and Engineers, EAGE, 2013)
The Subis Limestone is a Member of the Tangap Formation. It is Upper Oligocene to Lower Miocene in age. The Subis Limestone is divided into two sequences which are different in depositional setting and architecture. The lower sequence is Upper Oligocene in age, generally deep marine depositional environment and is for the most part in the subsurface. The upper sequence is Lower Miocene in age, shallow marine reefal depositional environment and forms a spectacular limestone hill that reflects the original carbonate platform. The geomorphology, sedimentology and sequence stratigraphy of the platform (upper sequence) are studied in detail in this paper. The platform is found to be a good analogue to the Sarawak offshore carbonate platforms that mark one of the main hydrocarbon provinces in Southeast Asia for containing large reserves of natural gas and -to a lesser extent-oil. Copyright Â© (2012) by the European Association of Geoscientists & Engineers All rights reserved.